The March On Washington: A Teacher’s Remembrance - Mugleston, William (Teaching History: A Journal of Methods, 1999)
Rarely does a history teacher have the opportunity of relating a historic moment first-hand to his or her students. In the summer of 1963 I was a 22-year-old newly minted college graduate, headed for work on a master’s degree that fall. As my home was in the suburbs of Washington, D.C., I had been able for several years to pick up summer jobs in the various federal agencies. That summer I was at the then Department of Health, Education and Welfare, doing just what, I have long forgotten. In that hot summer of the civil rights movement word had spread that there was to be a massive march on the nation’s capital.